Otro canon de peregrinos: El pelegrino curioso y su arte de mirar - Suárez Miramón, Ana (My University, 2017)
The work of Villalba represents a novelty in the Renaissance literary scene. His intention to travel for pleasure, just to see and record what he observes, leads him to make the first descriptions of the gardens of Aranjuez and the Abbey, of the theater shows and customs, while performing a courageous criticism of society at the same time that he breaks many of the subjects that were transmitted by tradition. This fusion of different elements together with a non-prejudiced sight of the world, turn him into an exception among the canon of genres and attitudes followed by his contemporaries., La obra de Villalba representa una novedad en el panorama literario renacentista. Su intención de viajar por gusto, para ver y registrar cuanto observa, le lleva a realizar las primeras descripciones de los jardines de Aranjuez y la Abadía, de espectáculos teatrales y de las costumbres, a la vez que realiza una valiente crítica de la sociedad y rompe con muchos tópicos transmitidos por tradición. Esa fusión de elementos dispersos y su mirada desprejuiciada lo convierten en una anomalía frente al canon de géneros y actitudes de sus contemporáneos.
Keywords: Non-canonical originality; travel; Villalba; Originalidad no canónica; viaje; Villalba